INDEKS KEPUASAN PENGGUNA LAYANAN PENDIDIKAN DI MTSN KOTA PROBOLINGGO - Soleha, Anik Matus; Andriyani, Desi Dwi; Kristiyono, Jefri Try (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2021)
The problem in this study is that the quality of education services in MTSN City of Probolinggo has an effect on service user satisfaction. The purpose of this study was to determine the satisfaction index of education service users which consisted of reliability, responsiveness, assurance, empathy, and tangible variables. The population of this study were all users of educational services, namely all students and guardians of students in MTSN Kota Probolinggo. This research is a descriptive quantitative research type with the instrument used in the form of a questionnaire. The data analysis method used in this research is the Community Satisfaction Index (IKM) in accordance with the Decree of the Minister of State Apparatus Empowerment Number: KEP / 25 / M.PAN / 2/2004. Community Satisfaction (IKM) is calculated using the weighted average value of each service element. The sample in this study were 150 respondents. The type of data used is primary data obtained through questionnaires. The results of the IKM research in MTSN City of Probolinggo have an education service satisfaction index value of 3.28 and an IKM value of 82 which means that the quality of service is included in category A, so that customer satisfaction with the quality of service can be said to be very satisfied. The conclusion of the research result shows that the quality of education services provided by MTSN Kota Probolinggo is very satisfying. Keyword : satisfaction index, IKM, users of education services